Challenges and a potential solution to perform drug susceptibility testing of omadacycline against nontuberculous mycobacteria. (December 2022) - Shankar, Prem; Singh, Sanjay; Boorgula, Gunavanthi D.; Gumbo, Tawanda; Heysell, Scott K.; Srivastava, Shashikant
Abstract: Background: Minimum inhibitory concentration (MIC) of slow growing mycobacteria (SGM) often do not correlate with the treatment response. Among the challenges is the identification of MIC of drugs that degrade in solution faster than the doubling time of the SGM. Methods: First, we identified the rate of omadacycline degradation in solution, and its effect on the rapidly growing methicillin resistant Staphylococcus aureus (MRSA). We then identified doubling times versus MICs for Mycobacterium abscessus, M. avium, and M. kansasii, with and without supplementation for degraded drug. Results: Omadacycline concentration in solution declined ∼50% over 24hr. In the MRSA experiments, omadacycline demonstrated 66.48 ± 19.38% loss in potency over 24hr, confirming the degradation rate in solution. M. abscessus had a doubling time of 8.75 ± 1.23hr and the omadacycline MIC after 24hr of incubation was 2mg/L with and without 50% daily drug supplementation, indicating that drug degradation had no effect on this rapid grower. The doubling time for M. avium was 29.52hr (95% confidence interval (CI): 23.18–33.89hr) and 31.15hr (95%CI: 19.45–38.49 hr) for M. kansasii . The M. avium MICs ±50% daily omadacycline supplementation were 1mg/L and 0.5mg/L on day 7, whereas the M. kansasii MICs ±50% daily supplementation were >128mg/L and 32mg/L on day 7. Conclusion: Omadacycline degradation in solution leads to falsely high MICs when SGM doubling time exceed the drug degradation rates in solution. The challenge could be overcome by daily drug supplementation to account for the loss of potency, which is laborious, or perhaps stabilizing the drug from degradation. Highlights: Omadacycline concentration in solution declined ∼50% over 24hr. M. avium and M. kansasii MICs ±50% daily omadacycline supplementation were 1mg/L versus 0.5mg/L and >128mg/L versus 32mg/L. Omadacycline degradation leads to falsely high MICs when slow growing mycobacteria doubling time exceed the drug degradation rates in solution.